Modular product design based on the supply chain network. (October 2017) - Rong, Zhijun; Yang, Zhiwei; Li, Ying; Chen, Kuisheng; Dan, Binbin
The modular design can shrink production and management costs by quick procession of the specific needs of individual end users. This article presents a modular product design approach to product-oriented supply chain network. The proposed approach first builds a relationship matrix through the functional and structural interaction between the product components. Second, module suppliers are determined by the product module division via fuzzy clustering analysis of the relationship matrix. Third, for the determined suppliers, the supply chain costs and lead time are obtained, which can indicate the pros and cons of the supply network. Thus, proposed optimal product modules are verified through the supply network. A case on refrigerator parts modular is examined by the proposed method.